Mus308 Processes Oxygen and Nitrogen Ethylation DNA Damage in Germ Cells of Drosophila - Nancy Díaz-Valdés; Miguel A. Comendador; L. María Sierra (Journal of Nucleic Acids)
The D. melanogaster mus308 gene, highly conserved among higher eukaryotes, is implicated in the repair of cross-links and of O-ethylpyrimidine DNA damage, working in a DNA damage tolerance mechanism. However, despite its relevance, its possible role on the processing of different DNA ethylation damages is not clear. To obtain data on mutation frequency and on mutation spectra in mus308 deficient (mus308-) conditions, the ethylating agent diethyl sulfate (DES) was analysed in postmeiotic male germ cells. These data were compared with those corresponding to mus308 efficient conditions. Our results indicate that Mus308 is necessary for the processing of oxygen and N-ethylation damage, for the survival of fertilized eggs depending on the level of induced DNA damage, and for an influence of the DNA damage neighbouring sequence. These results support the role of mus308 in a tolerance mechanism linked to a translesion synthesis pathway and also to the alternative end-joinig system.